Bully victimization and Internet addiction among adolescents: the chain mediating role of rumination and internalizing problems. - Huang, Zhaofei; Xu, Wei; Zhang, Jinxiu; Niu, Xiang; Wang, Jinliang (Psychology, Health & Medicine, 2026)
Background: Internet addictionelicits various physiological symptoms and mental health challenges,particularly among adolescents. Bully victimization, as an essential riskfactor for Internet addiction, has been receiving significant attention. However,the complex mechanisms between the two have not been fully explored. Objective: Thisstudy aims to examine the relationship between bully victimization andadolescent Internet addiction, specifically focusing on the chain mediatingrole of rumination and internalizing problems (anxiety and depression). Methods: Participantscomprised 6,620 Chinese middle school students (Mage = 14.53 years, SD = 1.85) and completed self-report questionnaires on bullyvictimization, anxiety, depression, and Internet addiction. Results: Thefindings reveal: (1) After controlling for age, bully victimization was positivelyrelated to adolescent Internet addiction; (2) Bully victimization has anindirect effect on Internet addiction through both rumination and Internalizingproblems, with a notable chain mediation involving rumination, anxiety, anddepression; (3) No significant gender differences were found in the chainmediating effects, as indicated by the analysis of multi-group effects. Conclusions: Theseresults underscore that bully victimization increases the risk of Internetaddiction and highlight the importance of preventive and interventionstrategies targeting rumination in managing adolescent Internet addiction.